Language Assessment Literacy: The Role of Self-Reflection - Kianinezhad, Neda (Universitas Bunda Mulia, 2023)
Language Assessment Literacy (LAL) is an indispensable component of an English language teacher's professional skill set. In recent decades, a significant volume of research has aimed to elucidate the dimensions of LAL, explore variations in teachers' LAL across diverse contexts, and identify supportive resources. This review will commence with a comprehensive analysis of varying conceptualizations and empirical investigations into teachers' understanding of the concept. Specifically, then, this review centers on the assessment training requirements of English language teachers, the effectiveness of current assessment training programs, and the role of self-reflection in fostering the growth of LAL among English language teachers. The findings of this review will offer a thorough overview of the existing body of literature and provide a foundation for future inquiries in the domain of language assessment literacy in English language teaching.